Modern Sample Preparation Approaches for Separation Science - Neng, Nuno (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
This book will provide the most recent knowledge and advances in Sample Preparation Techniques for Separation Science. Everyone working in a laboratory must be familiar with the basis of these technologies, and they often involve elaborate and time-consuming procedures that can take up to 80% of the total analysis time. Sample preparation is an essential step in most of the analytical methods for environmental and biomedical analysis, since the target analytes are often not detected in their in-situ forms, or the results are distorted by interfering species. In the past decade, modern sample preparation techniques have aimed to comply with green analytical chemistry principles, leading to simplification, miniaturization, easy manipulation of the analytical devices, low costs, strong reduction or absence of toxic organic solvents, as well as low sample volume requirements.Modern Sample Preparation Approaches for Separation Science also provides an invaluable reference tool for analytical chemists in the chemical, biological, pharmaceutical, environmental, and forensic sciences.